Hybrid interpenetrating hydrogel network favoring the bidirectional migration of tenocytes for rotator cuff tendon regeneration. Issue 2 (3rd August 2021) - Thankam, Finosh G.; Diaz, Connor; Chandra, Isaiah; Link, Josh; Newton, Joseph; Dilisio, Matthew F.; Agrawal, Devendra K.
Abstract: Replenishment of tenocytes to the injury site is an ideal strategy to improve healing response and accelerate the tendon ECM regeneration. The present study focused on the synthesis and characterization of a hybrid hydrogel scaffold system poly(propylene‐fumarate)‐alginate‐polyvinyl alcohol‐acrylic acid (PAPA) using poly(propylene‐fumarate) (PPF), alginate, polyvinyl alcohol (PVA) and acrylic acid and the in vitro investigation of bidirectional mobility of swine shoulder tenocytes (SST) for its potential application in rotator‐cuff tendon regeneration. IR analysis revealed the presence of alginate, PPF and PVA segments on the surface, SEM and AFM analyses revealed the porous and nano‐topographical features of PAPA, respectively, swelling was 712.6 ± 84.21% with the EWC (%) of 87.59 ± 1.26 having the diffusional exponent and swelling constant 0.551 and 1.8, respectively. PAPA was biodegradable, cytocompatible and supported long‐term survival of SSTs. SEM imaging revealed the adhesion, colonization, and sheet formation of SSTs within the PAPA hydrogel network. The SSTs seeded on the PAPA scaffolds were peculiar for their bidirectional migration as the anterograde movement was completed in 9 days whereas the retrograde infiltration occurred up to the depth of 198 μm. These findings suggest the promising translational potential of PAPA scaffold system in the management of rotator cuff tendon injury.